Geochemical Characteristics of Rare Earth Elements in Deep Geological Profile of Qitianling Intrusion, Hunan Province - HE Han-han; LI Jian-kang; LI Chao; SU Xiao-yun; ZHAO Zhi; ZHANG Yi-jun; WANG Guo-rui (Yankuang ceshi, 2014)
Baishidu-Feixianzhen profile in Qitianling intrusion of Hunan Province is one of the most important profiles carried out in Sinoprobe. Despite the fact that a large amount of previous research had been carried out using various methods on rare earth elements (REEs) characteristics of Qitianling granite complex, no systematical study has been undertaken on geochemical characteristics from different geological units including limestone, sandstone, quaternary eluvial clays, the plution and the weathering crust. Analysis of the REEs in the profile through Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) has been carried out and is reported in this paper. The results indicate that all geology units have LREE enrichment pattern, while a great difference exists between ΣREEs. For the total content of REEs in Qitianling Granite, the weathering crust has the highest level of ΣREEs with an average value of 605×10-6, and the limestone has the least ΣREEs with an average value of 154.3×10-6. In addition, the closer to the intrusions, the higher ΣREEs contents have in strata, even for the same lithology rock. In combination with REE-Y/ΣREE, ΣREE-δEu diagrams and Os Isotope tracer results, Qitianling granitoids might have mixed with some mantle materials. The content of REEs in the Qitianling Granite weathering crust (average value of RE2O3 is 814.8×10-6) are more than the cutoff grade of ion-absorbed-type REEs deposit (HREE RE2O3 0.05% and LREE 0.07%) in the main, which deserves further exploration.